Generalized periodic and generalized Boolean rings - Howard E. Bell; Adil Yaqub (International Journal of Mathematics and Mathematical Sciences)
We prove that a generalized periodic, as well as a generalized Boolean, ring is either commutative or periodic. We also prove that a generalized Boolean ring with central idempotents must be nil or commutative. We further consider conditions which imply the commutativity of a generalized periodic, or a generalized Boolean, ring.